Human resource practices in small businesses in Republic of North Macedonia - Piperkova, Irina; Djambaska, Elizabeta; Lozanoska, Aleksandra (Institute of Economics - Skopje, 2023)
The primary objective of this paper is to identify human resource practices implemented by small firms, so as to better understand the specifics of human resource management in small businesses. An online survey was conducted among small businesses in the Republic of North Macedonia. The research findings reveal that small firms in North Macedonia use employee referrals as a recruiting strategy and a traditional selection process based on CV/interview analysis. Most of small businesses have some form of consistent and continuous compensation system, with employee performance as a main criterion for determining the compensation level. Employee training has been identified as one of the biggest challenges that small businesses face. Most small firms conduct employee training to improve job-specific skills for current job tasks. In addition, employee trainings are implemented on an ad hoc basis and largely depend on firms’ available financial resources, since high training costs remain to be an obstacle to small firms.
Keywords: small business; human resource practices; Republic of North Macedonia